Mengatasi Darurat Kesenjangan Formasi ASN Guru Agama Katolik di Wonosobo: Kebijakan Afirmatif untuk Kualitas dan Keberlanjutan Pendidikan - Muslikun (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper describes that elementary education institutions (SD) in Wonosobo are facing an urgent crisis related to the availability of Catholic Religious Teachers with State Civil Apparatus (ASN) status, which requires immediate policy intervention. This article specifically identifies a significant gap between the real needs and the number of ASN teachers available. This condition directly threatens the quality of education and hinders the fulfillment of children's rights to receive proper religious instruction. Through a policy analysis approach, this article examines the national education and personnel regulatory framework. It compares data from related agencies such as the Ministry of Religious Affairs, the Ministry of Empowerment of State Apparatus and Bureaucratic Reform (KemenPAN-RB), and the Wonosobo Regency Education Office. The main focus of the analysis is on the root of the fundamental problem, namely the inadequacy of ASN formation and allocation, the limited quota of formations set by KemenPAN-RB, and the role of the Ministry of Religious Affairs which is still limited in the ASN appointment process. The writing methodology used is qualitative with a descriptive analysis approach, which not only describes the problem but also formulates concrete solutions. The results of the analysis show that the resolution of this problem, both in the short and long term, is highly dependent on the implementation of cross-sectoral coordinated affirmative policies. In conclusion, Wonosobo Regency is now facing a serious emergency in fulfilling the ASN Catholic Religious Teachers for Elementary Schools.